Smart City Policies in Realizing the Quality of Public Services in Yogyakarta City - Raissa Almira Deandra; Achmad Nurmandi; Helen Dian Fridayani (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2024)
Major cities around the world believe in the concept of "smart cities" or "intelligent cities." This concept encourages people to participate in city management through a citizen-centered approach with the aim of maximizing interaction and bringing the government closer to the people. This paper examines how the Yogyakarta City government can utilize e-government to transform into a smart city, enhancing its public services through the implementation of smart government, smart mobility, and smart living policies. Cities worldwide are actively promoting this concept as a central government initiative to tackle diverse issues in different regions. The analysis employs a qualitative approach, prioritizing data from digital mass media coverage regarding the implementation of smart cities. Next, we conducted the analysis using Nvivo 14 software. This paper reveals that (1) Smart Government, with its online procedures, has begun to function effectively; (2) Smart Mobility excels in traffic control; and (3) Smart Living is more prominent in security indicators. The application of smart city theory can facilitate the implementation of smart government, smart mobility, and smart living, thereby enhancing the quality of public services.